CONOCIMIENTOS Y PERCEPCIONES DE LOS ESTUDIANTES DE VIII A X SEMESTRE DE LA FACULTAD DE ODONTOLOGÍA DE LA UNIVERSIDAD SANTO TOMÁS SOBRE ADULTEZ MAYOR Y MANEJO ODONTOLÓGICO DE PACIENTES ADULTOS MAYORES (2018)
Objective: To evaluated the perceptions and knowledge of the elderly and the dental management from the eight to ten level of the Santo Tomas University students.Material and methods: An observational descriptive cross-sectional study was done. Ninety-three students were taken. The perceptions, knowledge and dental management about elderly were considered. The descriptive statistical analysis was done and chi square and t student test were taken to analyse each variable to sociodemographic characteristic.Results: The dental students from the Santo Tomas University were felt self confidence about clinical dental management in oral rehabilitations and endodontic treatments, had a good clinical cleverness to elderly patients. It was found a good knowledge about elderly in 8.6% of the students. The significance statistical difference were seen in perception by age (p=0.039) and oral and general perceptions by level (p=0.046).Conclusions: The Dentistry Program in the Santo Tomas University should continue promoting an integral vision of the elderly in order to developed and permitted to acquire the knowledge in the students about older and their oral clinical manage.